1997
DOI: 10.1016/s0009-9236(97)90044-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stiripentol on cytochrome P450-mediated metabolic pathways in humans: In vitro and in vivo comparison and calculation of in vivo inhibition constants*

Abstract: Stiripentol appears to inhibit several CYP450 enzymes in vitro and in vivo. In vivo inhibition constants show that stiripentol inhibition of CYP3A4 is linearly related to plasma concentration in patients with epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 42 publications
(3 reference statements)
2
55
0
1
Order By: Relevance
“…Similarly, the hepatic uptake of many lipophilic compounds is not necessarily restricted by protein binding (Kurz and Fichtl, 1983;Pacifici and Viani, 1992), and it has been found that the antifungal activity of itraconazole and ketoconazole is not diminished despite extensive binding albumin (Schäfer-Korting et al, 1995). In agreement, Tran et al (1997) have reported that the K i value of stiripentol obtained in microsomal studies is more consistent with total plasma concentration than unbound concentration. All these reports suggest that factors, other than protein binding, may be involved in a given biological process.…”
mentioning
confidence: 67%
“…Similarly, the hepatic uptake of many lipophilic compounds is not necessarily restricted by protein binding (Kurz and Fichtl, 1983;Pacifici and Viani, 1992), and it has been found that the antifungal activity of itraconazole and ketoconazole is not diminished despite extensive binding albumin (Schäfer-Korting et al, 1995). In agreement, Tran et al (1997) have reported that the K i value of stiripentol obtained in microsomal studies is more consistent with total plasma concentration than unbound concentration. All these reports suggest that factors, other than protein binding, may be involved in a given biological process.…”
mentioning
confidence: 67%
“…The approach used to calculate K i iv is based on the competitive inhibition model used previously (Adedoyin et al, 1987;Shaw and Houston, 1987;Kunze and Trager, 1996;Tran et al, 1997;Yao et al, 2001). The model includes the following assumptions: 1) product formation is described by Michaelis-Menten kinetics with competitive inhibition; 2) concentrations of (S)-mephenytoin are much lower than its K M ; 3) only one enzyme mediates the formation of 4-OH-meph; 4) after oral administration, the operating clearance of (S)-mephenytoin is its intrinsic clearance because (S)-mephenytoin has a relatively large clearance (Ito et al, 1998); and 5) fluvoxamine does not affect the elimination of 4-OH-meph.…”
Section: Calculation Of K I Iv Values For Cyp2c19mentioning
confidence: 99%
“…[16] STP mikrozomal sitokrom izoenzimlerinden CYP3A4, CYP1A2, CYP2C19'u inhibe eder. [17] STP birçok ilaçla etkileşime girer. STP'nin metabolizması enzim indükleyen AEİ'ler tarafından arttırılırken STP diğer AEİ'lerin metabolizmasını güçlü bir şekilde inhibe eder.…”
Section: Discussionunclassified